Correlación entre la radiación solar global y el número de días con precipitación pluvial (ING) - Wright, Jaime (1989)
This work measure the grade of association between experimental data of global solar radiation and number of days with precipitation in ten locations of Costa Rica; with the aim to establish relations for the estimation of the global solar radiation when these are not available.The results obtained using a cubic relation are satisfactories for all the actinometric stations analyzed in this work, for the estimation of the global solar radiation using the number of days with precipitation.It is recommended for future work, to prove the applicability of this statistical model in others actinometric stations of Costa Rica. This would allow one to estimate the global solar radiation in locations lacking with actinometric stations, but having the precipitation data.